PENDAMPINGAN IMPLEMENTASI POS SIKLUS PEMBELIAN BAHAN BAKU LOKAL PADA PERUSAHAAN TEKSTIL DI SURABAYA - Nugraheni, Bernadetta Diana Nugraheni Diana; Yudhanti, Ceicilia Bintang Hari; Wehartaty, Tineke; Handoko, Jesica (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service activity carried out at PT JIMAS is an activity to assist the implementation of the Standard Operating Procedure (SOP) cycle for purchasing local raw materials. This activity was carried out due to changes in procedures and documents and requests for new documents in the context of applying for ISO 9001:2015 certification. Assistance is provided to employees in the purchasing department of local raw materials. The goal is the employee to understand and carry out the new procedure and use the new document. Community service activities include making video tutorials and providing assistance to employees. Video tutorial explains the use of compliance checklists for both SOP and local raw material documents. The purpose of displaying SOP and these documents is to suit PT JIMAS current business environment conditions, as well as to help the company when conducting a compliance audit, the implementation of which is through audit documents in the form of a checklist of audit compliance. The results of this community service can help PT JIMAS in its internal control and as a requirement for ISO 9001; 2015.